Implementasi Metode Pembelajaran Ibnu Khaldun dalam Meningkatkan Daya Tanggap Peserta Didik pada Pembelajaran PAI - Rambe, Mgr Sinomba; Firdaus, Muhammad; Suhefri, Suhefri; Arfani, Arlinda Ayu Diah; Atika, Faizah Nur (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
The decline in students' responsiveness in understanding learning materials can hinder the achievement of learning objectives, often caused by the selection and use of inappropriate learning methods. This study aims to find learning methods that can improve students' responsiveness in PAI lessons at SD 100390 Sipiongot, based on Ibn Khaldun's learning methods. The research used descriptive qualitative methods with a case study approach through observation, interviews, and documentation. The results showed that some of the learning methods used at SD 100390 Sipiongot are: Repetition Method, which is applied to grades 1-3, improves memory. The Discussion Method, applied to grades 4-6, fosters critical thinking and improves responsiveness. The field trip method increases learners' responsiveness and provides new experiences.